Spatial spin flipping and spin switching phenomena on a Y-shaped graphene nanoribbon ferromagnetic junction with Rashba spin orbit coupling and strain. (28th June 2021) - Zhang, Lin; Tong, Peiqing
Abstract: We theoretically study a controllable spatial spin converter and spin valve by using a Y-shaped even-chain zigzag graphene nanoribbon (ZGR) junction with Rashba spin orbit coupling (SOC) and strain. By calculating the spin-dependent conductance spectra of different tunneling terminals through the multi-terminal Landauer formula, we find that the spin up electron can flip its spin orientation, and convert to spin down one on the left electrode, the same spin converting phenomena can be inhibited on the right terminal. The above spin flipping and its valve phenomena are derived from the interactions of the Rashba SOC, strain and magnetization layout. When the strain's orientation is along (perpendicular) to the zigzag chain's direction, the valley valve effect of the even-chain ZGR is remained, the Rashba SOC takes little effect on the spatial spin switching, one can get 100% polarized spin up (down) electrons at different terminals of the Y-shaped ZGR due to the valley valve effect. When the strain is changed to other direction, the valley valve effect is partly destroyed, Rashba SOC can enhance the spin flipping conductance and break the ON/OFF transport states of spin valve. Our investigations might be useful in designing a multi-parameter controllable spin valve and spin detector based on a multi-terminal graphene nanoribbon junction.